2020
DOI: 10.1016/j.xnsj.2020.100038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of translation and angular motion in loaded and unloaded positions in the lumbar spine

Abstract: Background Context: Abnormalities in intervertebral rotation and translation are important to diagnosis and treatment planning for common spinal disorders. Tests that do not sufficiently load the spine can result in misdiagnosed motion abnormalities. Upright flexion and extension x-rays are commonly used despite known limitations. Additional evidence is needed in support of preliminary studies suggesting that the change from standing to supine may sufficiently stress the spine to diagnose motion abnormalities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Of high importance with regard to selecting appropriate candidates for this intervention, knowledge of the pathological processes of symptomatic internal disc disruption and the capability to identify patients with earlier-stage lumbar discogenic pain [ 64 ] have advanced considerably during the course of the investigations summarized here. These existing and emerging assessments, outside of the scope of this present review, involve functional MRI, MR spectroscopy and other advanced imaging techniques [ 64 , 65 , 66 ], the radiographic assessment of sagittal translation, rotations, and instability and associated clinical tests [ 67 , 68 , 69 ], and provocation or anesthetic discography combined with computed tomography (CT discogram) [ 64 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of high importance with regard to selecting appropriate candidates for this intervention, knowledge of the pathological processes of symptomatic internal disc disruption and the capability to identify patients with earlier-stage lumbar discogenic pain [ 64 ] have advanced considerably during the course of the investigations summarized here. These existing and emerging assessments, outside of the scope of this present review, involve functional MRI, MR spectroscopy and other advanced imaging techniques [ 64 , 65 , 66 ], the radiographic assessment of sagittal translation, rotations, and instability and associated clinical tests [ 67 , 68 , 69 ], and provocation or anesthetic discography combined with computed tomography (CT discogram) [ 64 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have investigated the potential of measuring intervertebral motion by comparing images of the patient supine with images of the patient standing or exed. (102,(121)(122)(123) Some of those studies found that the greatest intervertebral translation was between upright and supine positions, while in other patients, the greatest translation was between upright exion and extension. Again, it is unknown whether rigorous, quality-controlled protocols would have changed the results.…”
Section: Supine-standingmentioning
confidence: 99%